Action-dependent Control Variates for Policy Optimization via Stein Identity - Liu, Hao; Feng, Yihao; Mao, Yi; Zhou, Dengyong; Peng, Jian; Liu, Qiang (ICLR 2018 Conference, 2018)
Policy gradient methods have achieved remarkable successes in solving challenging reinforcement learning problems. However, it still often suffers from the large variance issue on policy gradient estimation, which leads to poor sample efficiency during training. In this work, we propose a control variate method to effectively reduce variance for policy gradient methods. Motivated by the Stein’s identity, our method extends the previous control variate methods used in REINFORCE and advantage actor-critic by introducing more flexible and general action-dependent baseline functions. Empirical studies show that our method essentially improves the sample efficiency of the state-of-the-art policy gradient approaches.